Emerging Therapeutic Strategies for Attenuating Tubular EMT and Kidney Fibrosis by Targeting Wnt/β-Catenin Signaling - Hu, Lichao; Ding, Mengyuan; He, Weichun (Frontiers in Pharmacology, 2022)
Epithelial-mesenchymal transition (EMT) is defined as a process in which differentiated epithelial cells undergo phenotypic transformation into myofibroblasts capable of producing extracellular matrix, and is generally regarded as an integral part of fibrogenesis after tissue injury. Although there is evidence that the complete EMT of tubular epithelial cells (TECs) is not a major contributor to interstitial myofibroblasts in kidney fibrosis, the partial EMT, a status that damaged TECs remain inside tubules and co-express both epithelial and mesenchymal markers, has been demonstrated to be a crucial stage for intensifying fibrogenesis in the interstitium. The process of tubular EMT is governed by multiple intracellular pathways, among which Wnt/β-catenin signaling is considered to be essential mainly because it controls the transcriptome associated with EMT, making it a potential therapeutic target against kidney fibrosis. A growing body of data suggest that reducing the hyperactivity of Wnt/β-catenin by natural compounds, specific inhibitors, or manipulation of genes expression attenuates tubular EMT and interstitial fibrogenesis in the TECs cultured under profibrotic environments and in animal models of kidney fibrosis. These emerging therapeutic strategies in basic researches may provide beneficial ideas for clinical prevention and treatment of chronic kidney disease.